Pandangan Imam Syafi'i terhadap Perkawinan Wanita Hamil atas Pertimbangan Hakim dalam Mengabulkan Permohonan Dispensasi Kawin (Studi Putusan Penetapan Perkara Nomor: 70/Pdt.P/2023/PA.Sby) - Shova, Nurus; Mukarrom, Azmil (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In light of Imam Shafi'i's opinions on the topic of marriage law for pregnant women, this study seeks to understand why the judge approved the request for a marriage dispensation due to pregnancy. This research makes use of a qualitative methodology. Interviews are conducted as a means of gathering information. This study employs descriptive data analysis. Case Number: 70/Pdt.P/2023/PA, a marriage dispensation, is also investigated in this research. How Sby and the judge feel about pregnant women getting married, and how Imam Shafi'i feels about it. Based on the findings, it is legal to marry a pregnant woman, according to both Islamic law and the teachings of Imam Shafi'i on the subject of marriage. Nonetheless, the gender of the husband makes a difference. A man is considered to be the one who impregnates a woman if he marries her outside of a marriage contract, according to Law No. 1 of 1974 in the Compilation of Islamic Law. Imam Shafi'i, on the other hand, says that a man may legally wed a pregnant woman even if she impregnates him. It is advisable to wait for the baby to be born if a lady becomes pregnant as a result of talaq. others.